Physiopathological studies, characterization and yield loss assessment of Curvularia leaf spot of maize (Zea mays) - GARHWAL, P D; SHARMA, S S; DAHIMA, VINITA; YADAV, KALPANA; KHOKHAR, M K; GUPTA, RENU (The Indian Journal of Agricultural Sciences, 2022)
Curvularia leaf spot of maize (Zea mays L.) caused by Curvularia lunata var. aeria is one of serious foliar diseases of maize. An experimental conducted during 2016–17 at research farm of Maharana Pratap University of Agriculture and Technology, Udaipur, Rajasthan found that Curvularia showed considerable variation in growth characteristics, colony diameter and rate of sporulation. The maximum colony diameter was 90.0 mm with 11.0 × 104 conidia/mm2. The size measurement of conidia of C. lunata-01 was in range of 60.1–91.9 μm length and width range was 16.2–23.5 μm. Length and width of isolate C. lunata-02 recorded in range of 55.6–79.5 and 14.2–22.5 μm respectively. Host range distribution showed that pathogen has a wide host range in many crops and weeds under artificial inoculation. Seed transmission results showed that Local surya exhibited higher 66.66% seeds borne inoculam while Pratap makka-3 have 40.00% seed borne inoculums of pathogen. Physiopathological studies shows that 25±2°C was optimum temperature for both the isolates. Maximum mycelial growth and sporulation was found at 90% RH followed by 80% in both the isolates. The 22.29% losses in yield due to Curvularia leaf spot was assessed by using Le Clerg model. The present study of pathogen biology could be used by plant pathologists to develop or redesign management strategies for the maize growers.